Contribution of soft-bodied meiofaunal taxa to Italian marine biodiversity. Issue 1 (1st January 2020) - Curini-Galletti, M.; Artois, T.; Di Domenico, M.; Fontaneto, D.; Jondelius, U.; Jörger, K. M.; Leasi, F.; Martínez, A.; Norenburg, J. L.; Sterrer, W.; Todaro, M. A.
Abstract: Meiofauna includes an astonishing diversity of organisms, whose census is far from being complete. Most classic ecological studies have focused on hard-bodied Ecdysozoan taxa (notably Copepoda and Nematoda), whose cuticle allows determination at species-level after fixation, rather than soft-bodied, Spiralian taxa, which most often lose any diagnostic feature in fixed samples. Yet, metabarcoding studies have recently revealed a species-richness of soft-bodied taxa comparable, and in cases superior, to that of Copepoda and Nematoda together. However, given objective difficulties inherent to their study, which necessarily has to be performed on living individuals, and their limited utilisation for ecological and applicative research, taxonomic expertise on soft-bodied organisms has declined over the years, and diversity of these phyla in most areas of the world is presently completely unknown. Here we present an expert-based survey of current knowledge on the composition and distribution of soft-bodied meiofaunal taxa in Italy, with special references to the predominantly or exclusively meiobenthic phyla Gastrotricha, Gnathostomulida, Platyhelminthes, Rotifera, Xenacoelomorpha, and macrofaunal taxa with conspicuous meiofaunal representatives (Annelida, Mollusca and Nemertea). A total of 638 described species have been reported from Italian coasts; furthermore, the existence of a large number of undescribed species is mentioned. Knowledge of Annelida, Gastrotricha, and Rotifera appears particularly detailed, placing Italy among the best-known country worldwide. In contrast, knowledge of Platyhelminthes and Xenacoelomorpha appears patchy, and limited to few areas. Sampling effort has been uneven, with most species recorded from the Tyrrhenian Sea, while large sections of the Adriatic and Ionian seas have been poorly explored. Results highlight the role that Marine Biological Stations, notably the Zoological Station "Anton Dohrn" in Naples, have had in promoting the study of soft-bodied taxa in Italy.